KRITIK HARALD MOTZKI TERHADAP KLASIFIKASI MODEL PEMIKIRAN HADIS HERBERT BERG - Ahmad Ramzy Amiruddin; Muhammad Alfatih Suryadilaga (Ushuluna: Jurnal Ilmu Ushuluddin, 2021)
There are four classifications of hadith scholars measured by how skeptical they are of the authenticity of the hadith, namely Early Western Scepticism, Reaction Against Scepticism, Middle Ground, and Renewed Scepticism. Of the four classifications, Berg divides them into two groups, namely those who are skeptical and non-skeptical. In response to this, Harald Motzki specifically criticized Berg's classification. The data source that used is based on the article "The Question of The Authenticity of Muslim Traditions Reconsidered: A Review Article" by Harald Motzki as the primary source and the supporting articles for this article as a secondary source. Through the descriptive-analytical method, the writer will describe Harald Motzki's criticism of Herbert Berg's classification and provide an analysis of it, so that readers can understand the point of Harald Motzki's criticism and the reasons behind the criticism. With that method, it was found that Harald Motzki thought that if Berg's classification, both logically and epistemologically, was useless. This is based on three main criticisms: First, the unclear definition of the classification. Second, the error in capturing the meaning of the hadith scholars. Third, there is a bias in the skeptical group, so that the explanation for the non-skeptical group is not balanced.